Poesia e imagem: o anjo e o palhaço nas obras de Lília A. Pereira da Silva - Lopes, Job (2014)
Poetry and image are sublime ways of seeing the world, they comprehend elevated feelings, and resonate echoes. The poetics of contemporary writer Lília A. Pereira da Silva is the result of a deep surrender to written and visual arts; the author sets in her works the existential dramas, the wounds of time and the anguish of soul. Lília reveals with intense perception and simple sensitivity the man's interior hidden by the social masks, camouflaged by the persona and exposed by the shadow as in Jung's theory (2008). The images of the poet dialogue with emotions, they inhabit the human dwelling, they are like voices in the silence, and do not only express the double, but the triple as Rancière (2013) points out. The theoretical perspectives deal with criticism, sociology, phenomenology and hermeneutics as they consider the study of images subjectively within a constant process of interpretation in which the researcher has an essential role in the dialogue with the object studied. The research includes the analysis of eight poems and eight pictures by Lília Silva that makes up the literary corpus. Thus, the angel and the clown emerge as the main images in Lília s work: in poetry the angelic figure is constituted as a shadow, as the archetypal bearer of happiness and love, like a hero to save the lyrical self from the darkness of suffering. However, this idealization of the beloved/protector is a way that the poetic subject finds in trying to relive the past and believe in a prosperous future, that is, an inherent desire in every individual to hope for a fortunate future. In the pictorial images the clown is presented as an allegory of the melancholic modern man - anguished individual, enraptured by everyday boredom, lonely being facing an individualistic reality and suffering from social ills. "Each reader looks for something in the poem. And not unusually, he finds it: he already carried it inside him" (PAZ, 1982, p. 29). It is understood that when analyzing the angel and the clown two points of view are focused, one external with relation to the work and other internal - to the desires of the interior